Effectiveness of the Ageratum (Ageratum conyzoides) Leaf Extract as Botanical Fungicide Against Twisted Disease of Shallot - Rianosa Rianosa; Hartal Hartal; Setyowati Setyowati (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2020)
Rianosa R, Hartal H, Setyowati N. 2020. Effectiveness of the Ageratum (Ageratum conyzoides) leaf extract as botanical fungicide against moler diseases of shallot. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands 9(1): 1-10.Â Â Moler is a major disease of onion caused by Fusarium oxysporum f. sp. cepae. Application of synthetic fungicides in the long-term has a negative effect to the environment. Weed leaves of Ageratum (Ageratum conyzoides) have potential to be an anti-fungal, anti-bacterial as well as anti-cancer. This study aimed to determine the best concentration of Ageratum leaf extract to control twisted disease and to compare the effectiveness of botanical fungicide and synthetic fungicide. The research was conducted in June - September 2018 at the Plant Protection Laboratory and greenhouse, University of Bengkulu. The experiment was consists of five Ageratum leaf extract concentrations as a botanical fungicide (i.e. 1%, 2%, 3%, 4%, and 5%), and synthetic fungicide namely mancozeb and metil tiofanat and control treatment (in sterile soil with no fungicide treatment). The experiment used Completely Randomized Design (CRD) with a single factor. Ageratum leaf extract was obtained through the maceration method using ethanol 96%. The application of fungicide was carried out on shallot bulbs before planting. The results showed botanical fungicides from Ageratum leaf extract were effective against twisted disease of shallots, concentration 4% of Ageratum leaf extract resulted in a longer incubation period and lower disease intensity compared to other concentrations, and the effectiveness of Ageratum leaf extract at a concentration of 4% was comparable to that of mancozeb to control twisted disease. Application of both synthetic and botanical fungicide resulted in a higher yield of shallot. Therefore, Ageratum leaf extract has potential as a substitution of synthetic fungicides to control twisted disease of shallots.